J Neurol Res Rev Rep 2021
DOI: 10.47363/jnrrr/2021(3)132
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Associated Factors Among Refugees Amidst Covid-19 in Nakivale Refugee Camp in Uganda

Abstract: The COVID-19 pandemic and health measures to prevent it have unprecedented effects on the mental health of the refugees. However, the situation of refugees in developing countries is unclear. Thus, this study estimated the prevalence of and associated demographic factors during the COVID-19 pandemic. The study employed a cross-sectional survey carried out in June 2020 in which 146 adult refugees from Nakivale settlement camp were randomly selected to fill out a questionnaires-demographics and PHQ9. Results rev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Among the demographic characteristics of the respondents, older age (≥65 years) was associated with a decrease in depression or depressive symptoms ( 34 , 80 ) ( 35 , 45 , 59 , 81 , 94 ), while another study reported greater depression among middle-aged people (45–65 years) ( 58 ). The prevalence of depression was significantly higher among females than males ( 27 , 28 , 31 , 34 , 35 , 43 50 , 59 , 60 , 63 , 72 , 79 , 81 , 94 , 99 ). Marital status (i.e., being single, widowed, divorced, or separated) ( 59 , 67 , 79 ), living alone without family or having a lack of emotional support from family and society ( 71 , 97 ) ( 45 , 46 ), family size ≥ 3 ( 48 , 49 ) and living in an urban area ( 31 , 32 , 69 ) were found to significantly increase depression, with the exception of two studies ( 47 , 60 ) which indicated that married people were more than three times as likely to experience depression ( p < 0.05).…”
Section: Resultsmentioning
confidence: 96%
“…Among the demographic characteristics of the respondents, older age (≥65 years) was associated with a decrease in depression or depressive symptoms ( 34 , 80 ) ( 35 , 45 , 59 , 81 , 94 ), while another study reported greater depression among middle-aged people (45–65 years) ( 58 ). The prevalence of depression was significantly higher among females than males ( 27 , 28 , 31 , 34 , 35 , 43 50 , 59 , 60 , 63 , 72 , 79 , 81 , 94 , 99 ). Marital status (i.e., being single, widowed, divorced, or separated) ( 59 , 67 , 79 ), living alone without family or having a lack of emotional support from family and society ( 71 , 97 ) ( 45 , 46 ), family size ≥ 3 ( 48 , 49 ) and living in an urban area ( 31 , 32 , 69 ) were found to significantly increase depression, with the exception of two studies ( 47 , 60 ) which indicated that married people were more than three times as likely to experience depression ( p < 0.05).…”
Section: Resultsmentioning
confidence: 96%
“…In addition, a high prevalence of depression has consistently been found in the economically deprived groups in Uganda using the PHQ-9 at a cutoff of 10, such as refugees (range from 47% to 96%). 36,39,40 Individuals with depression who are involved in activities such as MSG to transition from poverty show a significant reduction in depressive symptoms (40.5% had recovered from depression in six weeks). 41 Despite this study recruiting women from an MSG, the prevalence of depression was high, a possible indicator of higher depression among women was not part of the MSG.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the country also has low levels of education to enable the majority of the population to comprehend the tool in its raw form-English (15). The country also has multiple refugee groups from different neighboring countries (e.g., Sudan, Democratic Republic of Congo, Rwanda, Burundi, Somali, and Ethiopia), all with different dialects (16)(17)(18)(19), and various disease conditions whose symptoms may lead to false positives with the tool such as TB and cancers, with masked symptoms such as loss of energy, anhedonia, loss of appetite, and poor sleep (12). In line with the issues mentioned above, the accuracy of depression detection by the PHQ-9 has limited generalizability.…”
Section: Introductionmentioning
confidence: 99%